Removal of arsenic from aqueous solution by adsorption on leonardite - Yuttasak Chammui (2018)
The present investigation deals with the uptake of As(III) and As(V) ions from aqueous solution at 25°C by a new prepared Leonardite char carbonized at 450°C. Arsenic adsorption experiments were carried out in batch systems to determine the amount of As(III) or As(V) adsorbed as a function of particle sizes of adsorbent, contact time and solution pH per fixed As concentration. In this study, the 75μm size of the Leonardite char was chosen since it had the maximum removal of As(III), whereas the removal of As(V) was close to 100%. The optimum equilibrium contact time and pH used for adsorption of both As(III) and As(V) were 3h and pH 7. The adsorption data showed good fit to both Langmuir and Freundlich isotherm models. The Langmuir monolayer capacities for As(III) and As(V) were estimated to be 4.46 and 8.40mg per gram of Leonardite char, respectively. The effect of SO42-, NO3- and Cl-as competing anions on As(III) and As(V) removal was also investigated at pH 7. The removal of arsenic due to these anions decreased in the following order: SO42->NO3->Cl-. Finally, the Leonardite char was applied successfully for arsenic removal from ground water samples. © 2013 Elsevier B.V.